Effect of hemicellulose extraction pretreatment on sulfonated corncob biochar for catalytic biodiesel production. Issue 1 (February 2023) - Cao, Minghe; Lu, Meizhen; Yin, Haojie; Zhu, Qinkai; Xing, Kainan; Ji, Jianbing
Abstract: In this work, waste corncob with high hemicellulose content was selected as the carbon source to investigate the effect of hemicellulose extraction on the prepared sulfonated biochar for biodiesel production. After hemicellulose extraction, the optimized sulfonated biochar with a maximum -SO3 H density of 2.05 mmol/g was synthesized under 3 h of carbonization at 300 °C, then 2 h of sulfonation at 90 °C. For the esterification, the 98.5% oleic acid equilibrium conversion was achieved under optimized reaction parameters: a 12:1 molar ratio (methanol/oleic acid) and a 10 wt% catalyst dosage at 65 °C for 4 h. The catalyst still reached 70% conversion efficiency after 10 cycles, which proved that the hemicellulose extraction not only played a role in the rational utilization of biomass but also the significantly-improved catalyst lifetime was beneficial to the sustainable production of biodiesel. Graphical Abstract: ga1 Highlights: Hemicellulose Extraction enables multi-stage utilization of biomass. Hemicellulose extraction as a pretreatment for the SCB-SO3 H catalyst. The optimized SCB-SO3 H catalyst has a sulfonic acid density of 2.05 mmol/g. The 98.5 % oleic acid conversion was obtained at optimal conditions. The SCB-SO3 H catalyst can be recycled 10 times with > 70 % conversion efficiency.